2020
DOI: 10.1155/2020/8345246
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CFTR Protects against Palmitate-Induced Endothelial Dysfunction by Enhancing Autophagic Flux

Abstract: Saturated free fatty acids (FFAs) elevate in metabolic symptom leading to endothelial dysfunction. Cystic fibrosis transmembrane regulator (CFTR) functionally expresses in endothelial cells. The role of CFTR in FFA-induced endothelial dysfunction remains unclear. This study is aimed at exploring the effects of CFTR on palmitate- (PA-) induced endothelial dysfunction and its underlying mechanisms. We found that PA-induced endothelial dysfunction is characterized by a decrease of cell viability, reduction of NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Oxidative stress due to overproduction of ROS acts as a key pathological mechanism in all stages of AS. While in normal physiology, ROS are important reactive molecules that regulate various cellular functions and processes, ROS-induced oxidative stress leads to vascular injury, inflammation, and foam cell formation. , Exposure to FFAs is well recognized as a trigger for overproduction of ROS, inflammatory response, and endothelial cell dysfunction . Recent research has suggested the use of various types of NSAIDs to inhibit oxidative stress in patients with AS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress due to overproduction of ROS acts as a key pathological mechanism in all stages of AS. While in normal physiology, ROS are important reactive molecules that regulate various cellular functions and processes, ROS-induced oxidative stress leads to vascular injury, inflammation, and foam cell formation. , Exposure to FFAs is well recognized as a trigger for overproduction of ROS, inflammatory response, and endothelial cell dysfunction . Recent research has suggested the use of various types of NSAIDs to inhibit oxidative stress in patients with AS .…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Exposure to FFAs is well recognized as a trigger for overproduction of ROS, inflammatory response, and endothelial cell dysfunction. 27 Recent research has suggested the use of various types of NSAIDs to inhibit oxidative stress in patients with AS. 28 Here, we report that feprazone might protect against ROS-mediated vascular injury by inhibiting the generation of ROS induced by FFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Functional endothelial CFTR limits oxidative stress and contributes to the normal anti-inflammatory state of human umbilical vein endothelial cells (HUVEC) [ 72 ]. Studies on HUVEC suggest a role for CFTR in maintenance of endothelial cell homeostasis [ 73 ], while other studies suggest CFTR upregulation protects against palmitate-induced endothelial dysfunction by improving autophagic flux [ 74 ]. Although CFTR impairment downregulates endothelial cell proliferation, migration and autophagy, defective CFTR function leads to endothelial cell activation and a persisting pro-inflammatory endothelium state with increased leukocyte adhesion.…”
Section: The Role Of Cftr In In Nonepithelial Cellsmentioning
confidence: 99%
“…NAD + reduces microvascular damage after cardiac I/R through restoring autophagic flux 171 . Forskolin protects against palmitate‐induced endothelial dysfunction by improving autophagic flux 76 . Thence, these observations implicated that targeting incomplete autophagy and reactivating autophagic flux may provide new mechanistic insights for potential therapeutic strategies for CVDs.…”
Section: Implications Of Incomplete Autophagy For Pharmacotherapymentioning
confidence: 99%